Case-Based Learning in Translational Biomedical Research Education: Providing Realistic and Adaptive Skills for Early-Career Scientists. (February 2019) - Greenberg-Worisek, Alexandra J.; Campbell, Katherine A.; Klee, Eric W.; Staff, Nathan P.; Schimmenti, Lisa A.; Weavers, Karen M.; Ekker, Stephen C.; Windebank, Anthony J.
Abstract : Problem: Case-based learning is an established means of educating students in law, business, and medicine; however, this methodology is not often applied to educating translational biomedical researchers. The application of case-based learning to translational biomedical research education allows scholars to actively engage with real-world material and apply their newfound knowledge as it is acquired. Approach: Through the Mayo Clinic Center for Clinical and Translational Science (CCaTS), three courses were delivered in 2009–2017 which emphasized case-based learning in clinical and translational science, entrepreneurship, and individualized medicine. Quantitative measures collected in student course reviews upon course completion were analyzed. Additionally, products arising from each course were identified, including publications and startups pitched. Outcomes: Analyses demonstrate that case-based learning techniques are well suited to graduate biomedical research education. Furthermore, case studies can be employed throughout the entire clinical and translational spectrum, from basic and preclinical work through to clinical and population-based learning. Next Steps: Within CCaTS, next steps include creating case-based courses in regulatory and team science to continue to allow scholars to learn and apply these critical skills to real-world material. The goal is to continue to provide immersive training opportunities in areas of clinical and translational science that cannot be readily learned in a traditional lecture-based class setting. Abstract : Supplemental Digital Content is available in the text.